Perancangan Sistem Informasi Akademik Pada Sekolah Menengah Pertama Berbasis Web - Ela Nurelasari (Computer Engineering Departement, Universitas Komputer Indonesia, 2020)
Information technology is advancing rapidly. The computer which is equipment that was created to facilitate human work, when achieving progress both in making hardware and software. Computer technology is very supportive in terms of data processing to create an information system that is used to provide maximum work results. The development of information technology is also influenced by the internet. With the internet we can provide services easily that can be accessed from anywhere in the world. Nowadays, almost everyone can access information, one of them through websites on the internet. By using information systems will easily get the information needed. Junior high school academic information system is one academic system that is very important for all information activities in school. The purpose and purpose of making the website is to provide a computerized new student registration system, can make it easier for students to see the value of learning outcomes without coming to school and make it easier for teachers to input student grades.